2018
DOI: 10.1021/acs.analchem.8b00935
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fishing for Peptides with Antibody-Immobilized Acrylate Monoliths, Coupled Online with NanoLC-MS

Abstract: An online microfluidics-mass spectrometry platform was developed for determining proteotypic peptides from in-solution digested samples. Accelerated and selective sample cleanup was achieved by integrating proteotypic epitope peptide immunoextraction with nano liquid chromatography-tandem mass spectrometry (online IE-nanoLC-MS/MS). Ten individually prepared 180 μm inner diameter capillaries with ethylene glycol dimethacrylate-co-vinyl azlactone (EDMA-co-VDM) monoliths were immobilized with anti-protein antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…This is in good agreement with another study mentioning that only 58% of the binding capacity remained after 10 uses (82). Similar results were reported for IS monoliths that were reused up to 50 times without observing any loss of trapping efficiency (60). In return, some authors observed losses after 5 (100,101) or even 3 (102) uses on pure samples.…”
Section: -Reusability Regenerationsupporting
confidence: 81%
See 1 more Smart Citation
“…This is in good agreement with another study mentioning that only 58% of the binding capacity remained after 10 uses (82). Similar results were reported for IS monoliths that were reused up to 50 times without observing any loss of trapping efficiency (60). In return, some authors observed losses after 5 (100,101) or even 3 (102) uses on pure samples.…”
Section: -Reusability Regenerationsupporting
confidence: 81%
“…This loss of performance after 3 uses was observed on 6 monoliths (whose performance was similar for the first uses) confirming this loss of performance. The results of the first use nevertheless illustrate the repeatability of the monolith preparation also reported by other groups (57,60). Concerning this last point, it can be considered that the commercialization of Sepharose based-ISs illustrates the reproducibility of their preparation.…”
Section: -Reusability Regenerationsupporting
confidence: 75%
“…better ionization or better digestion outcome). 12 Thirdly, the sample volume differs, 1000 mL in previously published method vs. 50 mL in the present method. Finally, two different LC-MS/MS systems are used the previously published methods employs an older triple quadrupole (TSQ Quantum Access, Thermo Scientic) coupled to a micro-LC while in the present paper a newer triple quadrupole (TSQ Quantiva) coupled to a nano-LC is used.…”
Section: Comparison Of Peptide Extraction With Protein Extractionmentioning
confidence: 81%
“…Additionally, immunoaffinity 90 and MIP 91 have been demonstrated in on-line LCMS systems making for automated and highly selective sample preparation. Other platforms have also been introduced such as chip-based MIP 92 and immunoaffinity 93 , immunoaffinity pipette tips (MSIA) 94 , beads 89, 95-97 and 96well plates 98 .…”
Section: Sample Preparation For Targeted Bottom-up Analysismentioning
confidence: 99%
“…However, the proposed cut-off value (upper normal limit of circulation) for ProGRP in serum has been established around 50-60 pg/mL 186,190,191 and therefore a sample preparing method providing clean extracts prior to MS detection is crucial due to the low abundance in serum. The protein was chosen as a model due to elaborate work on the protein in our group 89,90,97,192,193 and the analytical simplicities due to the lack of disulfide bridges. The protein also introduces some significant challenges by less favorable digestion in complex matrices (unpublished observations) compared to larger proteins with more cleavage sites and thus, a high performing tryptic digestion was needed for determinations.…”
Section: Pro-gastrin Releasing Peptidementioning
confidence: 99%